2013
DOI: 10.1080/13562517.2013.795939
|View full text |Cite
|
Sign up to set email alerts
|

White clinical psychology trainees' views on racial equity within programme selection in South Africa

Abstract: The issue of diversity in both physical and epistemological access to programmes in higher education is an important concern worldwide. In South Africa, as elsewhere, access to professional clinical psychology training programmes is extremely competitive, and there is an important imperative to diversify the student profile. Perspectives of black students on access to clinical psychology training in South Africa have been extensively studied, but the views of white students are minimally documented. We intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…However, the results from research questions 1 and 2 suggest that UKZN has been unable to produce Black African professional psychology graduates at the same rate that it has been able to produce Black African graduates overall. The possible reasons for these shortfalls can be attributed to factors pertaining to the nature of professional psychology recruitment and selection criteria and processes, and the availability of Black African individuals in the recruitment pool (Mayekiso et al, 2004; Padmanabhanunni et al, 2022; Pillay & Kramers, 2003; Pillay & Kramers-Olen, 2014; Pillay & Nyandeni, 2021; Pillay & Siyothula, 2008; Traub & Swartz, 2013). In terms of factors pertaining to the nature of selection criteria and processes, applicants with a strong academic record who can communicate and demonstrate the presence of ‘desirable’ qualities, such as warmth, empathy, stress management skills, self-reflexivity, and mastery of past psychological trauma (Cerrai, 1997; Ivey & Partington, 2014) are typically prioritised for selection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results from research questions 1 and 2 suggest that UKZN has been unable to produce Black African professional psychology graduates at the same rate that it has been able to produce Black African graduates overall. The possible reasons for these shortfalls can be attributed to factors pertaining to the nature of professional psychology recruitment and selection criteria and processes, and the availability of Black African individuals in the recruitment pool (Mayekiso et al, 2004; Padmanabhanunni et al, 2022; Pillay & Kramers, 2003; Pillay & Kramers-Olen, 2014; Pillay & Nyandeni, 2021; Pillay & Siyothula, 2008; Traub & Swartz, 2013). In terms of factors pertaining to the nature of selection criteria and processes, applicants with a strong academic record who can communicate and demonstrate the presence of ‘desirable’ qualities, such as warmth, empathy, stress management skills, self-reflexivity, and mastery of past psychological trauma (Cerrai, 1997; Ivey & Partington, 2014) are typically prioritised for selection.…”
Section: Discussionmentioning
confidence: 99%
“…Negative attitudes towards affirmative action (whether real or perceived) reportedly led to the stigmatisation of recipients when their competence was subtly questioned [3234]. The selection of students in accordance with what are viewed as racial quotas can be perceived negatively by other groups who are in competition for placements in registrar programmes, as has been reported in other professions [35]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that those students who previously enjoyed institutional privilege viewed transformation as a strategy aimed at dispossessing them of opportunities that they deserve (Cornell and Kessi 2017;Dirk and Gelderblom 2017;Durrheim et al 2011;Kohnert 2013;Robus and Macleod 2006;Thackwell et al 2016;Traub and Swartz 2013). A study conducted by Traub and Swartz (2013) into white psychology students' perceptions on racial equity in the psychology training programme at a South African university revealed that white students experienced uncertainty, internal shame at their privilege, and assigned blame to black students for being given unfair and unearned advantages.…”
Section: Understanding Progress Towards Attainment Of Transformationmentioning
confidence: 99%